Developing STEAM-based Students’ Worksheet with the Ecoprint Technique in Biology Subject - Irdalisa, Irdalisa; Amirullah, Gufron; Hanum, Erlia; Elvianasti, Mega; Maesaroh, Maesaroh (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This research aimed at developing a STEAM-based studentsâ€™ worksheet with the Ecoprint technique and analysing the developed product’s validity, feasibility and practicality. This research used the 4D development method (Define, Design, Develop, and Disseminate). The research subjects were 102 students of the tenth-grade science class in Senior High School. The instruments employed expert validation tests and questionnaires. The data were analysed by processing validator response data with a Likert scale converted into qualitative data. The results showed that the STEAM-based studentsâ€™ worksheet with the Ecoprint technique obtained a moderate level for its validity, while the feasibility aspects were 90% based on the studentsâ€™ views and 91% from the teachers. The results of the practicality test were 87% from the teachers and 92% by students, respectively. It can be concluded that the STEAM-based studentsâ€™ worksheets with the Ecoprint technique are valid, feasible and practical to use as a supporting learning media of Biology. Steam-based studentsâ€™ worksheet with the Ecoprint technique is very suitable to be applied as an innovative learning media which is relevant to 21st century demands by emphasising 4C skills.